Some experimental aspects of reproductive activity - San Martín F., Mauricio (1952)
Since 1940, when it was founded in Huancayo Laboratory of the Institute of Andean Biology, we have been interested in studies of reproductive physiology in relation to height, and as we progressed in our research, emphasized increasing the need for deepen this work, both in the field of endocrinology and early embryology, points began to study in 1947 with experience at sea level and were intended to serve as a baseline for future work at altitude, but the results we have been getting on these experiences, along with the spread and increasing use in the daily practice of medicine, not just products ganadotrópicos both equine and human origin, but also of ovarian hormone products, has led us to submit this thesis in the hope that it can serve as a contribution to elucidate concepts in the use of these hormonal products.